Hubungan Tingkat Stress terhadap Siklus Menstruasi di Asrama Putri Akper Almaarif - Siska Delvia; Azhari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
According to the health of reproduction WHO (World Health Organization) definition adolescence is from 12-14 years old. According to health is reproduction is Indonesian ( SKRRI) adolescence is from 14-15 years old. Research in japan from 221 respondence in stress condition almost 61% of students is university get menstrual irregular. This research was conducted to determine the relationship of stress with an irregular menstrual cycle on the students Akper Al-Maarif Baturaja. The research was conducted using the analytical method with a cross-sectional design. The population in this study is the students of the Faculty of Akper Al-Maarif, and the total sample used was 82 students who participated in this study and answering a set and complete questionnaires. At the very least. The study was conducted from May to June 2016. Data obtained from questionnaires that have been distributed to respondents. The computer program SPSS 16.0 helps the processing of the data. The results showed that 59,7% of respondents with stress were found and 40,2% of the respondents experienced an irregular menstrual cycle. Other results showed that 63% who didn't stress had irregular menstrual cycles (38% of them). Based on the results of the chi-square test, we found a significant relationship with the irregularity of the menstrual cycles in which the p-value is 0.003 (<0.05).